PENGELUARAN PENDIDIKAN BAGI ANAK ANGKAT DI INDONESIA, BENARKAH LEBIH BESAR DARI ANAK KANDUNG? - Maulana, Rizky; Ginting, Ika Rahma (UNIVERSITAS NEGERI SURABAYA, 2020)
Stigma has developed in the community that biological children are more loved and favoured by their parents than adopted children. Therefore, this study conducted to analyze the differences in education expenditure between biological and adopted children in Indonesia. Using IFLS 5 data, this study estimates the research model using multiple linear regression methods with OLS estimation. Estimation results show that adopted children get a higher portion of education expenses than biological children. This matter is contrary to the stigma that develops in society. Even though adopted children do not have natural ties with adoptive parents, their educational needs are still considered, even with higher expenditure than biological children.